2015
DOI: 10.1159/000430464
|View full text |Cite
|
Sign up to set email alerts
|

Calpain in Breast Cancer: Role in Disease Progression and Treatment Response

Abstract: The calpains are a family of intracellular cysteine proteases that function in a wide array of cellular activities, including cytoskeletal remodelling, survival and apoptosis. The ubiquitously expressed micro (µ)-calpain and milli (m)-calpain are archetypal family members that require calcium for function and can be inhibited by their endogenous inhibitor calpastatin. This review describes the role of the calpain system in the prognosis of breast cancer and disease progression, in addition to the role of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 97 publications
1
39
0
1
Order By: Relevance
“…Two members of the calpain family µ-calpain (calpain-1) and m-calpain (calpain-2) are ubiquitously expressed (11 (12). Investigations have demonstrated that calpain has a role in breast cancer progression, prognosis and treatment response, thus it is considered as a potential anticancer target (13). Furthermore, calpain activity is aberrantly higher in breast cancer tissues compared with normal breast tissues, and its expression correlates with metastatic phenotypic characteristics and increased invasive properties of tumors (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Two members of the calpain family µ-calpain (calpain-1) and m-calpain (calpain-2) are ubiquitously expressed (11 (12). Investigations have demonstrated that calpain has a role in breast cancer progression, prognosis and treatment response, thus it is considered as a potential anticancer target (13). Furthermore, calpain activity is aberrantly higher in breast cancer tissues compared with normal breast tissues, and its expression correlates with metastatic phenotypic characteristics and increased invasive properties of tumors (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the physiological functions of calpains are extensive, including regulation of apoptosis [31], cell migration [32], AR co-factor activation [33], and cell-to-cell communication via microparticle biogenesis [34,35] so on. Further exploration of the profound influence of triptolide on systematic function of cells or humans is still needed.…”
Section: Discussionmentioning
confidence: 99%
“…Calpains were identified to be involved in various biological processes, including cytoskeleton remodeling, signal transduction and cell apoptosis (68). Currently, 16 family members have been identified (9), which are classified into two types: The classical calpains and the non-classical calpains (4,5,1015). Due to slight variations in their structure, the various calpains were identified to be associated with various physiological activities.…”
Section: Introductionmentioning
confidence: 99%